A MULTIMEDIA MELTING POT: TECHNOLOGY TO DAZZLE AND DRAMATIZE. - Rudofski, A.H.; al, et (ETC: A Review of General Semantics)
Presents the author's experience of a symposium on interactive multimedia, sponsored by the Society for Technical Communication, that was a day-long feast of leading-edge technology, current applications, and future directions. Descriptions; Costs; What interactive media is used for; More.